2016
DOI: 10.1016/j.jco.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Lower bounds for the approximation with variation-diminishing splines

Abstract: We prove lower bounds for the approximation error of the variationdiminishing Schoenberg operator on the interval [0, 1] in terms of classical moduli of smoothness depending on the degree of the spline basis using a functional analysis based framework. Thereby, we characterize the spectrum of the Schoenberg operator and investigate the asymptotic behavior of its iterates. Finally, we prove the equivalence between the approximation error and the classical second order modulus of smoothness as an improved versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…We generalize some results of the manuscript [17], where spectral properties of this kind have been shown concretely for the variation-diminishing Schoenberg operator in order to show the limit of the iterates and to prove lower bounds for their approximation error in terms of different moduli of smoothness. If these spectral properties have been established, we apply the famous Theorem of Katznelson and Tzafriri [11] that states that the iterates converge in the operator norm if and only if the spectrum of T has either no points on the unit circle or 1 is the only spectral value on the unit circle.…”
mentioning
confidence: 76%
“…We generalize some results of the manuscript [17], where spectral properties of this kind have been shown concretely for the variation-diminishing Schoenberg operator in order to show the limit of the iterates and to prove lower bounds for their approximation error in terms of different moduli of smoothness. If these spectral properties have been established, we apply the famous Theorem of Katznelson and Tzafriri [11] that states that the iterates converge in the operator norm if and only if the spectrum of T has either no points on the unit circle or 1 is the only spectral value on the unit circle.…”
mentioning
confidence: 76%
“…Finally, we want to compare our result to a related result that has been shown recently in the case of non‐uniform knots. Nagler et al showed that for all f ∈ C ([0,1]) and n, the following estimate holds: ω2f,δmink·1γnormalΔn,kdk1/28·fSnormalΔn,kf0,1, where γΔn,k is the second largest eigenvalue of Schoenberg variation‐diminishing spline operator SΔn,k with knot sequence Δn={}xjj=kn1, ie, γnormalΔn,k:=supλ:λσ(SnormalΔn,k)1, and δmin denotes the minimal mesh length of the knots, δmin:=min(xj+1,kxj,k):j0,,n1. Note that t...…”
Section: The Lower Bound Of the Approximation Error Of The Schoenbergmentioning
confidence: 99%
“…Furthermore, there exists upper bounds for the approximation error with the second‐order modulus of smoothness, see eg, Esser . Recently, such estimates have been shown in Nagler et al and Zapryanova and Tachev, while the results in both articles do not provide computable constants. In this article, we show lower estimates of the uniform spline approximation error in terms of the second‐order modulus of smoothness.…”
Section: Introductionmentioning
confidence: 99%
“…Nagler et al [10] proved the convergence of the iterates of the Shoenberg operator to the operator of linear interpolation at the endpoints of the interval [0,1]. Their approach uses the result of C. Badea [1].…”
Section: Introductionmentioning
confidence: 99%